2021
DOI: 10.3390/jof7070558
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Siderophore Conjugates for Theranostic Applications in Invasive Pulmonary Aspergillosis Using Low-Molecular TAFC Scaffolds

Abstract: Invasive pulmonary aspergillosis (IPA) is a life-threatening form of fungal infection, primarily in immunocompromised patients and associated with significant mortality. Diagnostic procedures are often invasive and/or time consuming and existing antifungals can be constrained by dose-limiting toxicity and drug interaction. In this study, we modified triacetylfusarinine C (TAFC), the main siderophore produced by the opportunistic pathogen Aspergillus fumigatus (A. fumigatus), with antifungal molecules to perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…In conclusion, recognition of ferrioxamines by Sit1 does not involve the termini of linear ferrioxamines, and modification of the termini does not block their uptake. These findings are possibly helpful for generating conjugates of ferrioxamines with toxic molecules to design novel antifungal drugs with microbial uptake specificity in a Trojan horse approach [ 26 , 53 ]. In this respect, it is noteworthy that SITs are fungal-specific transporters [ 10 ]; ferrioxamines are also used by bacteria but the transporters are of different types [ 54 , 55 ] and might have different characteristics for conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, recognition of ferrioxamines by Sit1 does not involve the termini of linear ferrioxamines, and modification of the termini does not block their uptake. These findings are possibly helpful for generating conjugates of ferrioxamines with toxic molecules to design novel antifungal drugs with microbial uptake specificity in a Trojan horse approach [ 26 , 53 ]. In this respect, it is noteworthy that SITs are fungal-specific transporters [ 10 ]; ferrioxamines are also used by bacteria but the transporters are of different types [ 54 , 55 ] and might have different characteristics for conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that A. fumigatus internalizes several fluorescent and nonfluorescent TAFC derivatives, including fluorescent [Fe]DAFC-FITC ( 16 18 ). Epifluorescence microscopy demonstrated that the internalization of [Fe]DAFC-FITC depends on MirB but not MirD ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, epifluorescence microscopy revealed that MirB-mediated transport tolerates the conjugation of fluorescent FITC to TAFC (DAFC-FITC). Moreover, previous studies indicated that A. fumigatus internalizes several other fluorescent and nonfluorescent TAFC derivatives ( 16 18 ). These results emphasize the translational potential of SITs for the development of a novel antifungal drug mechanism based on the conjugation of toxic compounds to siderophores.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the efficient uptake of a radiolabeled siderophore by a pathogen is crucial for effective imaging, these findings might help to improve the properties of siderophores used for imaging. In a proof-of-concept study, Pfister et al previously demonstrated that certain siderophores could be used in a theranostic approach, in which antimicrobial therapy is combined with a diagnostic approach [ 38 ]. In this study, 68 Ga-imaging was combined with the fusion of antimicrobials to the siderophore to exploit the so-called Trojan horse approach.…”
Section: Discussionmentioning
confidence: 99%